(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This study explores the intricate relationship between food tourism and traveler motivations, focusing on the distinctions between "survivors" and "enjoyers." While some travelers merely exhibit a casual interest in food, others consider local cuisine and food experiences integral to their holiday experiences. López-Guzmán and Sánchez-Canizares (2012) identify three traveler segments: survivors, enjoyers, and experiences, shedding light on diverse interests and motivations related to food. The literature review emphasizes the economic impact of food tourism, highlighting its potential to foster job opportunities, showcase regional restaurants, and contribute to local economies. The study acknowledges the varied attitudes of travelers towards food, underlining the expanding interest in food tourism and its multifaceted significance for travelers. Ultimately, this research provides insights into the complex interplay between food tourism, economic benefits, and the diverse motivations of travelers, particularly the distinct preferences of "enjoyers" and "survivors" in the realm of culinary experiences.